2021
DOI: 10.1016/j.xcrm.2021.100263
|View full text |Cite
|
Sign up to set email alerts
|

GIPR antagonist antibodies conjugated to GLP-1 peptide are bispecific molecules that decrease weight in obese mice and monkeys

Abstract: Lu et al. show that tackling obesity with bispecific molecules that antagonize/ agonize GIPR/GLP-1R pathways decreases body weight and metabolic parameters in obese mice and monkeys. Mechanistic studies suggest that such molecules bind to GIPR and GLP-1R simultaneously and trigger receptor internalization, amplifying endosomal cAMP signaling in cells expressing both receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“… 58 A GLP-1R agonist/GIPR antibody (antagonist) fused protein was reported promoting body weight loss. 59 Nevertheless, whether a GLP-1R agonist/GIPR antagonist can improve T2DM needs more evidences. A GLP-1R agonist/GIPR antagonist peptide is theoretically possible but few full-length GIP-like antagonists were reported, 60 therefore it requires an array of attempts, at least an alanine-scan experiment of GIP with measuring of affinity.…”
Section: Plausible Orientationsmentioning
confidence: 99%
“… 58 A GLP-1R agonist/GIPR antibody (antagonist) fused protein was reported promoting body weight loss. 59 Nevertheless, whether a GLP-1R agonist/GIPR antagonist can improve T2DM needs more evidences. A GLP-1R agonist/GIPR antagonist peptide is theoretically possible but few full-length GIP-like antagonists were reported, 60 therefore it requires an array of attempts, at least an alanine-scan experiment of GIP with measuring of affinity.…”
Section: Plausible Orientationsmentioning
confidence: 99%
“…Recent data indicate that inhibition of GIPR signaling, either alone or in combination with GLP1R agonism, can contribute to the induction of body weight loss in both mouse and cynomolgus monkey models of obesity, and therefore GIPR is a target of interest for the treatment of obese patients. 9,11,17 To determine if antibody-mediated inhibition of GIPR in adult male mice could replicate the findings in Gipr Adipo-/- with muGIPR-Ab have demonstrated that doses ≥25 mg/kg every 6 days was sufficient to prevent body weight gain in a diet-induced obese mouse model. 17 The 300 mg/kg dose was chosen to ensure maximum inhibition of GIPR activity in the testis and was known to be a well-tolerated dose in CD1 mice.…”
Section: Chronic Gipr Antagonism In Adult Mice Does Not Impact Male M...mentioning
confidence: 99%
“…Both hormones stimulate insulin secretion from pancreatic β‐cells while GIP also promotes triglyceride storage in adipocytes 8 . Notably, both GIP receptor (GIPR) agonists and antagonists similarly prevent weight gain in pre‐clinical models and are actively being pursued clinically for the treatment of obesity 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Previously, GIP was described as an obesity hormone 7,8 . In recent years, paradoxically, both GIP receptor (GIPR) agonism and GIPR antagonism have shown anti‐obesity effects when combined with GLP‐1RAs in preclinical models 9‐13 . Potentially, the beneficial effects of GIPR agonists arise from functional GIPR antagonism elicited by GIPR internalization 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In recent years, paradoxically, both GIP receptor (GIPR) agonism and GIPR antagonism have shown anti-obesity effects when combined with GLP-1RAs in preclinical models. [9][10][11][12][13] Potentially, the beneficial effects of GIPR agonists arise from functional GIPR antagonism elicited by GIPR internalization. 14,15 Several new treatment modalities for type 2 diabetes and obesity combining GLP-1RA with GIPR agonism or GIPR antagonism are emerging.…”
Section: Introductionmentioning
confidence: 99%